Liberalization Only at the Margins? Analysing the Growth of Temporary Work in German Core Manufacturing Sectors. (8th June 2016) - Benassi, Chiara
Abstract: Drawing on workers' surveys and workplace interviews, this article investigates the growth of temporary work in German manufacturing sectors since the 1980s. Findings partly confirm a 'dualization' scenario as workers without industry‐specific vocational training are more likely to be on a temporary contract than skilled workers, and the gap has widened over time. However, also skilled workers have become increasingly vulnerable to casualization due to job routine and the erosion of industrial relations. Evidence confirms the crucial role of institutions in supporting the linkage between specific skills and employment stability, and suggests that the liberalization of the employment relationship has the potential to advance also in the core of the German economy.